Analysis of Pandemic’s Impact on Financial Performance of Public and Private Telecommunications Companies in the Period 2018-2020 - Indri Purnamasari, Dian; Fitriani, Nisrina Zulfa (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study aims to compare the financial performance of public and private telecommunications companies during the Covid 19 pandemic from 2018 to 2020. The results indicate that, in terms of liquidity ratio, no significant differences were found in financial performance between public and private telecommunications companies during the pandemic. With regard to solvency ratio, no differences in financial performance were found between public and private telecommunications companies during the pandemic. In respect of profitability ratio, differences in financial performance were found between public and private telecommunications companies during the pandemic. Lastly, in terms of activity ratio, no significant differences were found in financial performance between public and private telecommunications companies during the pandemic.